InfoSec career hacking sell your skillz, not your soul - Bayles, Aaron W.; Brindley, Ed.; Foster, James C.; Hurley, Chris; Long, Johnny (Rockland, MA : Syngress Pub., 2005)
Do you spend hours coding on an application for the sheer joy and challenge? How about taking the time to analyze every piece of traffic that crosses your network, dissecting packets, and making sure nothing hidden is going on? If you want to refine these skills (and learn many new ones) to build an InfoSec career in a top corporation or government agency but aren't sure where to begin, this book is for you! The authors of this book have all succeeded in applying their inherent, hacker skills to build successful InfoSec careers. From them, you will learn about the many, different jobs availabl.
The targets : what I want to be when I grow up (or at least get older) -- Reconnaissance : social engineering for profit -- Enumerate : determine what's out there -- First Strike : basic tactics for successful exploitation -- The laws of security -- No place like /home : creating an attack lab -- Vulnerability disclosure -- Classes of attack -- Don't trip the sensors : integrate and imitate -- Vulnerability remediation : work within the system -- Incident response : putting out fires without getting burned -- Rooting : show me the money!
Keywords: Computer hackers; Computer security; Electronic books